Analysis of The Influence of Consumer Spending Patterns, Marketing Strategy Effectiveness, and Product Inoventory Management on Sales Revenue Growth During The Holy Month of Ramadhan at Ethica Store in Pamekasan - Kurniawati Kurniawati; Rini Aprilia Lestari; Yulanda Elis Meyena (Dinasti International Journal of Digital Business Management, 2026)
This study analyzes the effect of consumer patterns, marketing strategy effectiveness, and product stock management on sales revenue growth during the fasting month at Ethica Store Pamekasan in 2025. This study uses a quantitative approach with multiple linear regression analysis to test the partial effect of each independent variable on sales revenue. The t-test results show that consumer patterns have a positive and significant effect on sales revenue (t=10.000 > p=0.000), the effectiveness of marketing strategies also has a positive and significant effect (t=5.651 > p=0.000), as does product stock management, which has a positive and significant effect (t=7.040 > p=0.000). These findings indicate that the increase in sales revenue during the fasting month is mainly influenced by changes in people's consumption patterns, supported by effective marketing strategies and proper stock management. The implications of this study emphasize the importance of monitoring Ramadan consumption trends, optimizing promotions, and ensuring product availability in order to maximize sales opportunities